2010
DOI: 10.1007/s11605-010-1196-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Benign Disease in Patients that Underwent Resection for Presumed Pancreatic Cancer Diagnosed by Endoscopic Ultrasonography (EUS) and Fine-Needle Aspiration (FNA)

Abstract: Even with aggressive use of preoperative evaluation, there is still a small subset of patients where malignancy cannot be excluded without pancreaticoduodenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…25,43 Furthermore, recent studies have shown that, in the pancreas, benign tumors with inflammatory findings are often misinterpreted radiologically as having vascular invasion and that 5% to 13% of pancreatic resections with a clinical diagnosis of "cancer" prove to be benign, and, in the majority, radiologic "vascular invasion" was the primary cause of the erroneous cancer classification. [56][57][58] We suspect that the latter phenomenon is most likely in play in these cases. In fact 5% of our SCNs were also thought to be "malignant on imaging" but did not show any evidence of malignancy by histology or behavior.…”
Section: Discussionmentioning
confidence: 89%
“…25,43 Furthermore, recent studies have shown that, in the pancreas, benign tumors with inflammatory findings are often misinterpreted radiologically as having vascular invasion and that 5% to 13% of pancreatic resections with a clinical diagnosis of "cancer" prove to be benign, and, in the majority, radiologic "vascular invasion" was the primary cause of the erroneous cancer classification. [56][57][58] We suspect that the latter phenomenon is most likely in play in these cases. In fact 5% of our SCNs were also thought to be "malignant on imaging" but did not show any evidence of malignancy by histology or behavior.…”
Section: Discussionmentioning
confidence: 89%
“…On subsequent analysis, they reported a 2.2% rate for surgical-cytologic discordance for pancreatic parenchymal lesions. Similarly, de la Fuente et al 13 found that 7% of patients with pancreatic lesions detected by EUS and/or EUS-FNA actually had benign disease on a pancreaticoduodenectomy. Interestingly enough, findings in the Gleeson et al trial closely mirrored our results, in that, on review of discordant cases, the main cause for FP results was interpretation errors by the pathologist in the setting of chronic pancreatitis.…”
Section: Discussionmentioning
confidence: 89%
“…A report from Duke University reported 494 patients who underwent Whipple procedure for suspected malignancy between 1992 and 2007 and showed that despite the use of aggressive preoperative work-up for pancreatic cancer, up to 7% of patients that undergo resection will have benign disease on postoperative pathologic examination. All of these patients had findings concerning for malignancy on both CT scanning and endosonography preoperatively [16]. In 2 more recent European studies, prevalence of benign disease in patients who underwent pancreatoduodenectomy for presumed malignancy reported to be 8.4% [17] and 15.6% [6].…”
Section: Discussionmentioning
confidence: 99%